Pengaruh Game Online Terhadap Motivasi Belajar,Interaksi Sosial dan Perilaku Keberagamaan Hindu Siswa Kelas XI SMA (SLUA) Saraswati 1 Denpasar. - Ida Bgs Gde Suwitrisna Putra; Wayan Paramartha; Ni Putu Suwardani; Ida Ayu Gde Yadnyawati (UHN I Gusti Bagus Sugriwa Denpasar, 2024)
This online game is a modern game that has become a trend nowadays and its fans range from children to adults. With the rise of online games among students, the author visited SMA (SLUA) Saraswati 1 Denpasar. Why was SMA (SLUA) Saraswati 1 Denpasar chosen, because SMA (SLUA) Saraswati 1 Denpasar is the oldest private high school in Denpasar, and to this day still exists among the community. The location of SMA (SLUA) Saraswati 1 Denpasar is in the city center and around it there are places to play online games. Based on several research results, it was found that online games have an influence on learning motivation, social interaction, student behavior, therefore this research wants to prove 1. Is there an influence of online games on student learning motivation? 2. Is there an influence of online games on students' social interactions? 3. Is there an influence of online games on students' religious behavior? This research design is quantitative research. Data collection methods use questionnaires, observation and literature. Data analysis uses inferential statistical analysis, namely regression. The results of hypothesis testing regarding the influence between Online Games and Learning Motivation show that the research hypothesis has been tested, namely that there is a positive influence of Online Games on the Learning Motivation of class 11 students at SLUA Saraswati Denpasar, statistically proven by the results of linear regression analysis where the tcount value is 19.682 while the ttable is 1.960. Because ttable is smaller than tcount (1.960 <19.682) and significance (sig.) 0.000 < 0.05 so H0 is rejected and Ha is accepted. This means that there is a significant positive influence of the Online Game variable (X) on Learning Motivation (Y1). There is an influence of online games on social interaction. The results of the hypothesis test show that the tcount value is 13,682, while the ttable is 1.960. Because ttable is smaller than tcount (1.960<13,682) and significance (sig.) 0.000 <0.05, there is a significant positive influence of the Online Game variable (X) on social interaction (Y2). There is an influence between online games on students' religious behavior. Hypothesis test results show that the tcount value is 14,734 while ttable is 1.960. Because ttable is smaller than tcount (1.960<14,734) and significance (sig.) 0.000 <0.05. This means that Ho is rejected and Ha is accepted, so there is a significant positive influence of the Online Game variable (X) on Hindu Religious Behavior (Y3).